Why Should I Accept Ads on my Mobile Phone? Factors Affecting the Acceptance by Brazilian Teenagers - Hor-Meyll, Luis Fernando (2014)
Among the more than six billion cellular phone lines in the world, around 220 million are found in Brazil. These numbers draw the attention of companies and academics, seeking to understand how cell phones can be used as an advertising media. This study sought to discover factors that could affect the intention of Brazilian teenagers to accept advertisements via SMS messages.  A survey was conducted on a sample of 385 students of a high school in Rio de Janeiro. The results of an analysis via structural equations suggest that attitude toward mobile advertising, perceived utility of the message and social norms are the factors with greater impact on the likelihood of teenagers to accept advertisements via SMS.